Fluorescent labeling of asbestos fiber for enhanced asbestos detection under fluorescence microscopy - Kuroda, Akio (Frontiers in Public Health, 2025)
The application of fluorescence microscopy (FM) for detecting micro- and nano-scale inorganic materials has historically been limited by the lack of specific fluorescent probes. However, recent research has demonstrated that asbestos-binding proteins can act as effective fluorescent probes, significantly enhancing the sensitivity and selectivity of FM for asbestos fiber detection. This advancement enables the identification of nano-scale fibers at lower magnifications, reducing the labor costs associated with asbestos contamination detection. Based on these advantages, two FM-based methods have been developed: (i) phase-contrast microscopy (PCM)-FM, a differential counting approach fully compatible with PCM-based epidemiological data, and (ii) portable FM, which shows strong potential for rapid on-site asbestos screening. Additionally, FM may enable multicolor labeling and live-cell fluorescent imaging of asbestos, opening new avenues for asbestos research. Despite these advancements, several challenges remain. Fluorescent probes alone cannot definitively identify asbestos, and issues such as cross-reactivity need to be addressed. This review highlights future perspectives and challenges for advancing FM methods in asbestos detection and research.